BRS 327: a new bread wheat cultivar - Silva,Márcio Só e (2010)
Wheat cultivar BRS 327 resulted from a cross between CEP 24 and BRS 194. 'BRS 327' has high yield, white flour and belongs to the bread class. The mean grain yield in the four years of evaluation was 3,998 kg ha-1.